MRI in lung cancer: a pictorial essay - Hochhegger, Bruno; Marchiori, E.; Sedlaczek, Oliver; Irion, K.; Heussel, C. P.; Ley, Sebastian; Ley-Zaporozhan, Julia; Soares Souza, A.; Kauczor, Hans-Ulrich (British journal of radiology, 2011)
Imaging studies play a critical role in the diagnosis and staging of lung cancer. CT and 18-fluorodeoxyglucose positron emission tomography CT (PET/CT) are widely and routinely used for staging and assessment of treatment response. Many radiologists still use MRI only for the assessment of superior sulcus tumours, and in cases where invasion of the spinal cord canal is suspected. MRI can detect and stage lung cancer, and this method could be an excellent alternative to CT or PET/CT in the investigation of lung malignancies and other diseases. This pictorial essay discusses the use of MRI in the investigation of lung cancer.
Published online: 28 Jan 2014
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.09.2022